2015
DOI: 10.1109/tpds.2014.2333011
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Movement for Target Coverage and Network Connectivity in Mobile Sensor Networks

Abstract: Abstract-Coverage of interest points and network connectivity are two main challenging and practically important issues of Wireless Sensor Networks (WSNs). Although many studies have exploited the mobility of sensors to improve the quality of coverage and connectivity, little attention has been paid to the minimization of sensors' movement, which often consumes the majority of the limited energy of sensors and thus shortens the network lifetime significantly. To fill in this gap, this paper addresses the chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 37 publications
0
124
0
Order By: Relevance
“…Besides, it also completes the effective coverage of the whole monitoring area by adjusting the adjustable parameter. Satisfying the presupposition of the network connection, Liao et al 18 complete the coverage of goal nodes by taking advantages of the moving characteristic of the sensor nodes. Thus, it proposes the heuristic algorithm, taking the Thiessen polygon as the active area to reduce the sensor nodes' energy consumption to balance the network energy, proposing the sensor network coverage.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, it also completes the effective coverage of the whole monitoring area by adjusting the adjustable parameter. Satisfying the presupposition of the network connection, Liao et al 18 complete the coverage of goal nodes by taking advantages of the moving characteristic of the sensor nodes. Thus, it proposes the heuristic algorithm, taking the Thiessen polygon as the active area to reduce the sensor nodes' energy consumption to balance the network energy, proposing the sensor network coverage.…”
Section: Methodsmentioning
confidence: 99%
“…However, in 2014, Liao et al [9] have found a small number of works on minimizing the sensor mobility. Hence, they started investigating the mobile sensor deployment (MSD) problem to obtain the minimal movement and the maximum network connectivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Steiner minimum tree method is constructed to solve the network connectivity problem. In 2014, Temel et al [5] studied works related to deterministic sensor deployment [9], and found out that the implementation of that method in 3D environment has not yet been accomplished. So, they proposed a deterministic sensor deployment method, which is based on wavelet transform (WT) to maximize the quality of coverage of a WSN with a minimum number of sensors on a 3D surface.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This dissertation topic mainly focuses on minimization of sensors' movement to provide target coverage and network connectivity. For this, the Mobile Sensor Deployment (MSD) problem is defined to deploy mobile sensors to provide target coverage and network connectivity at minimum movement cost [1]. The formal definition of the MSD problem is as below.…”
Section: Proposed Systemmentioning
confidence: 99%